Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Godoy Altamirano, María Claudia (2019)
In recent years, there has been an increase in the international demand for agricultural products because they present high nutritional values. The society presents a trend of healthy consumption and concern for the environment. This has allowed the agro-export industry to detect opportunities to enter to new markets with diversified products, managing to meet the needs of customers. Camposol is a Peruvian agro-export company recognized worldwide for its high quality products, nutritional value and sustainable, supported by international certificates of quality, research and development, economies of scale thanks to its technology. According to what has been analyzed, its main strengths are its diversified portfolio of products from fruits and vegetables to seafood, it has solid commercial alliances and international commercial offices that allow it to provide a better level of customer service. On the other hand, there are enriching opportunities for Camposol as a greater number of trade agreements between Peru and other countries, an increase in the trend of healthy consumption, therefore, high demand and facilities for export. Its main strategy is based on cost reduction, thanks to its high-tech processing plants, which allows it to increase the productivity and adequate yield of its crops, managing to meet the demand of its retail customers and distributors. It should be noted that Camposol has a trajectory of constant changes in its organization, so a restructuring is essential, to allow better coordination between the areas and adequate performance of its employees, generating greater productivity and flexibility.